Cell Wall Teichoic Acid Glycosylation in Listeria monocytogenes Serotype 4b Requires gtcA, a Novel, Serogroup-Specific Gene - Promadej, N. (American Society for Microbiology, 1999)
We have identified a novel gene, gtcA, involved in the decoration of cell wall teichoic acid of Listeria monocytogenes serotype 4b with galactose and glucose. Insertional inactivation of gtcA brought about loss of reactivity with the serotype 4b-specific monoclonal antibody c74.22 and was accompanied by a complete lack of galactose and a marked reduction in the amounts of glucose on teichoic acid. Interestingly, the composition of membrane-associated lipoteichoic acid was not affected. Complementation of the mutants with the cloned gtcA in trans restored galactose and glucose on teichoic acid to wild-type levels. The complemented strains also recovered reactivity with c74.22. Within L. monocytogenes, sequences homologous to gtcA were found in all serogroup 4 isolates but not in strains of any other serotypes. In serotype 4b, gtcA appears to be the first member of a bicistronic operon which includes a gene with homology to Bacillus subtilis rpmE, encoding ribosomal protein L31. In contrast to gtcA, the latter gene appears conserved among all screened serotypes of L. monocytogenes.